2010
DOI: 10.1016/s1674-8301(10)60026-7
|View full text |Cite
|
Sign up to set email alerts
|

Vascular smooth muscle cell differentiation – 2010

Abstract: Vascular smooth muscle cells have attracted considerable interest as a model for a flexible program of gene expression. This cell type arises throughout the embryo body plan via poorly understood signaling cascades that direct the expression of transcription factors and microRNAs which, in turn, orchestrate the activation of contractile genes collectively defining this cell lineage. The discovery of myocardin and its close association with serum response factor has represented a major break-through for the mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 108 publications
0
13
1
Order By: Relevance
“…Therefore, because Klf4 binding to the CArG box and subsequent inhibition of SM-specific gene transcription is regulated by its relative abundance, high expression of the SM-specific genes is most often associated with low VSMC proliferation and migration rates whereas low expression of SM-specific genes is most often associated with high proliferation and migration rates. 23 miR-145 did not effect Klf5 expression in our study, nor did Klf5 change in response to RI suggesting that in contrast to Klf4, Klf5 does not play a role in VSMC phenotype regulation during CCG. Other studies have reported differential regulation of Klf4 and Klf5.…”
Section: Discussioncontrasting
confidence: 68%
“…Therefore, because Klf4 binding to the CArG box and subsequent inhibition of SM-specific gene transcription is regulated by its relative abundance, high expression of the SM-specific genes is most often associated with low VSMC proliferation and migration rates whereas low expression of SM-specific genes is most often associated with high proliferation and migration rates. 23 miR-145 did not effect Klf5 expression in our study, nor did Klf5 change in response to RI suggesting that in contrast to Klf4, Klf5 does not play a role in VSMC phenotype regulation during CCG. Other studies have reported differential regulation of Klf4 and Klf5.…”
Section: Discussioncontrasting
confidence: 68%
“…There has been significant progress in understanding the hallmarks of the phenotypic modulation of SMC and the complex mechanisms involving the regulatory circuits of transcription factors and crosstalk of intracellular signalling pathways [1][2][3][4][5]. The main characteristics of differentiated SMC are the presence of a rich array of myofilaments and expression of a cytocontractile proteome that is necessary for the principal function of these cells, namely contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Other established SMC differentiation marker proteins, namely smMHC, h-caldesmon [1][2][3][4] and dedifferentiation marker protein calmodulin [26], were also affected by changes in Tcadherin expression. Compared with their respective control E transductants Tcad+-SMC exhibited decreased levels of smMHC and h-caldesmon and elevated levels of calmodulin ( Fig.…”
Section: T-cadherin Upregulation Leads To Decay Of Smc Differentiatiomentioning
confidence: 98%
See 1 more Smart Citation
“…To determine whether PDGFRa þ cells represented a distinct population of interstitial cell, we performed double-label immunohistochemistry using antibodies against smooth muscle myosin II heavy chain (Smmhc), a specific marker for SMCs [34] and c-Kit, to identify ICCs, which are the pacemaker cells in the oviduct [26,35]. PDGFRa þ cells did not express considerable Smmhc, supported by a significant fold decrease in Myh11 expression in oviduct and uterus (Table 3), suggesting they were distinct from SMC in these organs.…”
Section: Peri Et Almentioning
confidence: 99%